Research on the Overtopping-Induced Breaching Mechanism of Tailings Dam and Its Numerical Simulation - Zhao Deng; Shiqiang Wu; Ziwu Fan; Zhikun Yan; Jingxiu Wu (Advances in Civil Engineering)
The centrifugal model test system is utilized to reappear the breaching process of a tailings dam. The results show that there are significant differences in breaching processes between tailings dams and earth-rockfill dams. Influenced by the special physical and mechanical properties of tailings, the breaching processes of tailings dams are of short duration, and the flood flow through the breach increase rapidly. Based on the centrifugal test results, considering the special physical and mechanical properties of tailings, a mathematical model for tailings dam breaching is established. In the model, the vertical undercutting and horizontal expansion are simulated utilizing the erosion rate formula which is derived from shear stress principle of water flow; limit equilibrium method is used to analyze the breach slope stability. In addition, the model adopts iterative calculation method to simulate the whole breaching process. The analysis results show that, the proposed model is applicable in modeling the dam breaching process for tailings dam due to overtopping.